Анализ измерительных схем автоматических хемилюминесцентных газоанализаторов оксидов азота и озона - Mikhejeva, I. L.; Kurinnyy, V. K.; Tayakin, V. Yu.; Mazyra, L. D. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
The features of constructing measuring structures of chemiluminescent gas analyzers for monitoring nitrogen oxides and ozone in atmospheric air, in automobile exhaust gases, and in industrial emissions are considered. The characteristics of modern gas analyzers produced by various companies are presented.